Transformation Of Accounting Information For Business Development: A Qualitative Study Of Digital Platform-Based Entrepreneurship - Inang Aria Arifin; Natan Tebai; Siti Nurhayati; Bunga Aditi; Margo Saptowinarko Prasetyo (International Journal of Management and Business Economics, 2026)
Digital transformation has changed the pattern of modern business management, including the use of accounting information as a basis for business decision-making. The development of digital platforms, e-commerce, cloud accounting, and technology-based information systems encourages entrepreneurs to adapt to financial management systems that are more effective, efficient, and integrated. This study aims to analyze the transformation of accounting information as a business development tool in platform-based digital entrepreneurship. The research method used is a descriptive qualitative approach with a literature study. Data were obtained from various scientific sources such as national and international journals, books, and academic articles relevant to digital transformation, accounting information systems, and digital entrepreneurship. Data analysis techniques were carried out through data reduction, data presentation, and interpretative conclusion drawing. The results indicate that the transformation of accounting information significantly impacts the effectiveness of business management, the quality of decision-making, operational efficiency, and business adaptability in the digital economy environment. The implementation of digital accounting information systems enables real-time data integration, improves financial transparency, and supports innovation in digital platform-based business models. However, the transformation still faces several challenges, including low digital literacy, limited human resources, data security issues, and technology implementation costs. Therefore, strengthening digital capacity and sustainable technology adaptation strategies are necessary so that entrepreneurs can optimally utilize accounting information for business development in the digital era.